Harm compensation issues after a terrorist act by russian law - G. Demieva, Ainur (2018)
The experience of international regulation of security issues almost forms the basis for the legal regulation of national law in the cases where the problems of the relationship between an individual and a state are characterized by critical problems arising from the spread of terrorism. States consider the problems of protection from terrorism as actually formed ones, that is, the availability of information about the actions of groups of terrorists, the facts and the criminal links related to terrorist acts, as well as direct terrorist attacks that occurred on the territory of countries. States apply various forms of combat with terrorism uniformly, including generally recognized models of proclaiming in constitutions or in other acts the legitimate duty of the state to respect and protect human rights, the inviolability of an individual, and the guarantee of life, health and freedom safety. In reality, the opportunities of a state are not realized fully on their own, as the authorities themselves recognize their inability to solve the problem of terrorism unilaterally, spreading additional "burden" on the introduction of specific actions on the part of citizens, public organizations, civil society institutions and local bodies for terrorist act prevention. Today we have to admit that the problem of terrorism will not be completely eradicated and in the short term it is necessary to have a comprehensive legal regulation to counteract terrorism, including the reparation to terrorist victims